Evaluation of phosphorus efficiency in soybean (Glycine max) and wheat (Triticum aestivum) cropping system in relation to fertilizer on a Typic Haplustert - RAO, A SUBBA; REDDY, K SAMI; TAKKAR, P N (The Indian Journal of Agricultural Sciences, 2013)
In a field experiment in a semi-arid climute on a Typic Haplustert, several means of measuring phosphorus efficiency were evaluated in soybean [Glycine max (L.) Merr.]- wheat (Triticum aestivum L. emend, Fiori & Paol.) cropping system in relation to applied p, Seven rates of P (0, 10, 20, 40, 60, 80 and 100 kg P/ha) were applied to both the crops, The computed optimum fertilizer P rates to achieve 90% of the maximum yield were 32,5 to 33.5 kg P/ha for soybean and 49.5 to 44.5 kg P/ha for Wheat during the 2 years. More applied P was translocated to grain in wheat than in soybean. The efficiency of fertilizer - P utilization in both the crops was reduced beyond 40 kg P/ha. Wheat proved more efficient in utilizing the fertilizer P and also required larger dose of fertilizer P, whereas soybean efficiently utilized the soil P and required lower rate of the fertilizer P.